House dust microbiota and atopic dermatitis; effect of urbanization. Issue 5 (9th March 2021) - Mahdavinia, Mahboobeh; Greenfield, Leah R.; Moore, Donyea; Botha, Maresa; Engen, Phillip; Gray, Claudia; Lunjani, Nonhlanhla; Hlela, Carol; Basera, Wisdom; Hobane, Lelani; Watkins, Alexandra; Mankahla, Avumile; et al.
Abstract: Background: Previous studies have shown that a child's risk of developing atopic disease is impacted by both genetic and environmental factors. Because small children spend the majority of their time in their homes, exposure to microbial factors in their home environment may be protective or risk factors for development of atopic diseases, such as atopic dermatitis. Methods: Dust samples from the homes of 86 Black South African children 12 to 36 months old were collected for analysis of the bacterial microbiome. This case‐control study design included children with and without atopic dermatitis from rural and urban environments. Results: Significant differences in bacterial composition and diversity were found when comparing children with and without atopic dermatitis. Furthermore, house dust microbiota was significantly different in rural and urban areas. Differences were best accounted for by higher relative abundance of Ruminococcaceae, Lachnospiraceae, and Bacteroidaceae families in rural compared with urban houses. Levels of Ruminococcaceae were also found to be significantly depleted in the house dust of rural children with atopic dermatitis as compared to control children. Conclusions: House dust composition may be an important risk factor for the development of atopic disease, and this association may be driven in part by the gut microbiome. Low levels of the Ruminococcaceae family from Clostridia class in particular may explain the association between urban living and atopy. However, further research is needed to elucidate these links.